Nursing care for a normal postpartum patient (Mrs N) in Arafah 2 Inpatient Ward at Dr. Zainoel Abidin Regional General Hospital of Banda Aceh - Fitri Wahyuni; Darmawati Darmawati; Dewi Hermawati (Indonesian Journal of Health Science, 2026)
Optimal postpartum care is fundamental to preventing complications, facilitating maternal recovery, and promoting mother’s independence during the puerperium. Accordingly, comprehensive and evidence-based postpartum nursing care is required. This case study aimed to apply holistic nursing care using the nursing process approach in a normal postpartum patient, Mrs N, in Arafah 2 Inpatient Ward of dr. Zainoel Abidin Regional General Hospital, Banda Aceh. The assessment revealed a blood pressure of 121/76 mmHg, pulse rate of 85 beats per minute, respiratory rate of 22 breaths per minute, body temperature of 36.8°C, the patient presented with a first-degree perineal rupture with-healed suture, lochia rubra, and intermittent perineal pain with a pain score of 4 during movement. The identified nursing diagnoses included postpartum discomfort, ineffective breastfeeding, and knowledge deficit related to postpartum care. Evidence-based nursing interventions consisted of breathing relaxation techniques and Qur’an recitation to reduce postpartum discomfort, oxytocin massage and breast care to enhance breast milk production, as well as nutritional counseling—particularly protein intake—and perineal wound care to improve postpartum self-care abilities. The evaluation demonstrated that postpartum discomfort was resolved, ineffective breastfeeding was partially resolved, and knowledge deficit was resolved. Comprehensive and evidence-based postpartum nursing care is recommended to enhance maternal comfort, support successful breastfeeding, and promote optimal recovery during the postpartum period.